APPLICATION OF THE TALAQQI METHOD IN IMPROVING THE ABILITY TO READ THE QUR'AN AT SDN 046415 BATUKARANG - Aprianto (Journal of Quality Islamic Education Research, 2024)
In this study there are many new methods in improving the ability to read the Qur'an, while in reality traditional methods such as the talaqqi method are very good if applied in improving the ability to read the Qur'an. The purpose of the problem in this study is to find out how the application of the talaqqi method in improving the ability to read the Qur'an at SDN 046415 Batukarang. And to find out the inhibiting and supporting factors of this talaqqi method in improving the ability to read the Qur'an, the researcher used the action research method. Data collection using observation methods, diaries, oral test data, and documentation, the results of the study showed that: The application of the talaqqi method in improving the ability to read the Qur'an of students at SDN 046415 Batukarang by carrying out four stages, namely the planning stage, action, observation, and the last is the reflection stage. Inhibiting factors include laziness, tiredness and sleepiness. And supporting factors are the availability of adequate facilities and infrastructure, good quality coaching in the field of tajwid, fashahah and teaching staff according to their fields.